Six footprints to monitor the bioeconomy into a safe and just future - Helander, Hanna; Beck-O’Brien, Meghan; Lutz, Christian; Schaldach, Rüdiger; Schomberg, Anna; Többen, Johannes; Bringezu, Stefan (Frontiers in Environmental Science, 2025)
Environmental footprints should play a key role in monitoring the bioeconomy. They can capture environmental pressures and impacts of biomass production and extraction, as well as provide comparable per capita values disclosing how biomass use is distributed globally. As such, footprints could help ensure a sustainable transition and implementation of the bioeconomy. To develop national bioeconomy monitoring systems, we suggest six specific indicators and revise the state-of-art as regards their methodological development, as well as assess their applicability and feasibility for contributing to a systemic monitoring. Drawing on several years of collaborations between researchers from the different footprint domains, we introduce an integrated modelling approach to link global trade models for national footprint accounting with spatially specific impact assessments of terrestrial biomass production. The integrated approach captures all six indicators as it combines pressure indicators (forest- and agricultural biomass, agricultural land use and greenhouse gas emissions) and spatially specific impact indicators (water scarcity and biodiversity). This comprehensive and manageable set of footprint indicators addresses the main sustainability challenges of the bioeconomy developments.